Overexpression of salicylic acid methyltransferase reduces salicylic acid-mediated pathogen resistance in poplar - Dong, Huixia; Zhang, Wei; Li, Yongxia; Feng, Yuqian; Wang, Xuan; Liu, Zhenkai; Li, Dongzhen; Wen, Xiaojian; Ma, Shuai; Zhang, Xingyao (Frontiers in Plant Science, 2022)
Salicylic acid (SA) is generally considered to be a critical signal transduction factor in plant defenses against pathogens. It could be converted to methyl salicylate (MeSA) for remote signals by salicylic acid methyltransferase (SAMT) and converted back to SA by SA-binding protein 2 (SABP2). In order to verify the function of SAMT in poplar plants, we isolated the full-length cDNA sequence of PagSAMT from 84K poplar and cultivated PagSAMT overexpression lines (OE-2 isolate) to test its role in SA-mediated defenses against the virulent fungal pathogen Botryosphaeria dothidea. Our results showed that after inoculation with B. dothidea, OE-2 significantly increased MeSA content and reduced SA content which is associated with increased expression of SAMT in both infected and uninfected leaves, when compared against the wild type (WT). Additionally, SAMT overexpression plant lines (OE-2) exhibited higher expression of pathogenesis-related genes PR-1 and PR-5, but were still susceptible to B. dothidea suggesting that in poplar SA might be responsible for resistance against this pathogen. This study expands the current understanding of joint regulation of SAMT and SABP2 and the balance between SA and MeSA in poplar responses to pathogen invasion.